Bimekizumab for the treatment of moderate to severe psoriasis: a real-world experience over 52 weeks from two Italian dermatology clinics - E. Mortato; F. Artosi; C. Borselli; I. Compagnucci; Antonia Rivieccio; C. Lanna; S. Lambiase; R. Gaeta Shumak; F. Loconsole; L. Bianchi; E. Campione (Journal of Dermatological Treatment)
Purpose: Psoriasis is a chronic, immune-mediated inflammatory skin condition marked by erythematous, scaly plaques. This retrospective observational study evaluated the long-term efficacy and safety of bimekizumab, a dual IL-17A and IL-17F inhibitor, in treating moderate to severe plaque psoriasis in 56 patients across two dermatology clinics in Italy. Materials and methods: Adult participants with a baseline Psoriasis Area and Severity Index (PASI) >10, or <10 with sensitive area involvement, were followed for 16 to 52 weeks. Clinical outcomes were measured by PASI 75, 90, and 100 responses and Dermatology Life Quality Index (DLQI) scores at 4, 16, 36, and 52 weeks. Results: At week 16, 97.5% of patients achieved PASI 75, 76.7% reached PASI 90, and 66% attained PASI 100. By week 52, 91.5% achieved PASI 90 and 85.1% reached PASI 100, with 95.7% reporting a Dermatology Life Quality Index (DLQI) score of 0 or 1, indicating minimal impact on daily life. The study found similar efficacy across bio-naïve and bio-experienced groups, and between normal-weight and obese patients, without statistically significant differences. The safety profile was consistent with previous trials, with oral candidiasis as the most frequent adverse event (21%). Conclusions: These findings support the efficacy and tolerability of bimekizumab for long-term psoriasis management.